Muslim consumers’ purchase behavior towards halal cosmetic products in Malaysia - Haque, A. K. M. Ahasanul; Anwar, Naila; Tarofder, Arun Kumar; Ahmad, Nor Suhana; Sharif, Sultan Rahaman (Growing Science Publishing Company, 2018)
Over the years, substantial efforts have been given for exploring the halal concepts particularly, in the aspect of consumable goods and services. Concerning the issue of halal cosmetic products, the majority of the studies were undertaken until the stage of consumers’ purchase intention only. Comparatively, only few studies were found in the area of pertaining to Muslims’ purchase behavior of halal cosmetic products. Hence, this study can be considered significant in the sense that it tries to bridge this gap in the existing literature. Therefore, this study gives some new insights to the current body of knowledge by focusing on purchase behavior of halal cosmetics. The findings of the study demonstrate that attitude, perceived behavioral control, and religiosity had significant relationships with purchase intention, whereas subjective norm had an insignificant relationship. Ultimately, the findings would be helpful for generating future researches and offering supplementary resources, especially in the Malaysian context.